Active teaching through mathematical problems in primary school - Dograshvili, Tamar (Special Education, 2020)
Active teaching is a key component in the education system at all stages of education. In practice, introduction of active teaching in mathematics teaching in primary school poses significant challenges for teachers. To solve this problem, we have developed a methodological approach described in this article. In particular, we suggest an active teaching model whose realization is linked to the inclusion of problems with developmental and interdisciplinary content in the teaching process in mathematics classes. The solutions of these problems are associated with particular themes in mathematics classes. We discuss the methodology for constructing the systems of problems with developmental and interdisciplinary content in accordance with particular themes in mathematics classes in primary school, which is based on the scheme that we developed. We have also analyzed the indicators of including such problems in mathematics classes in primary school and the results of the educational experiment demonstrating that the author’s methodological approaches provide a high quality of mathematical education for primary school pupils, make the teaching process interesting and attractive, and ensure their involvement in the process of active teaching and learning through the systems of specially selected problems.